COUSTOMER’S ATTITUDE TOWARDS FINTECH IN ISLAMIC BANKS IN DISTRICT PESHAWAR - Gulalay Javed; Sanam Wagma Khattak (International Journal of Contemporary Issues in Social Sciences, 2024)
Financial technology innovations aim is to compete with traditional procedures in the delivery of financial services. In Pakistan Islamic banking sector is progressing rapidly and Islamic banks are in intense competition with the conventional banking sector. The customers of Islamic banks want the best financial products. Keeping in view the customer’s attitude of Islamic banks and profitability of Islamic banks this research tried to explore the customer’s attitude towards fintech in terms of usefulness, easiness, and risk in Islamic banks along with demographic and socio-economic factors like age, education, family income and employment status. Using the convenient sampling technique, 245 questionnaires were filled from different customers of Islamic banks. The descriptive statistic, cross-tabulation and regression analysis were used to analyze the data. The calculated results identified that easiness, risk and usefulness effect the use of financial technology. The results showed that financial technology is useful in making Islamic banks profitable. The results also highlighted important guidelines and information for Islamic banks, to formulate better policies and strategies to improve products and services to attract the potential ones in future.